1995
DOI: 10.1016/0301-0104(94)00333-6
|View full text |Cite
|
Sign up to set email alerts
|

Theory of second harmonic generation in randomly oriented species

Abstract: It is well known that second harmonic generation (SHG) is a process forbidden within atomic and molecular fluids. Nonetheless recent experimental observations of second harmonic evolution in suspensions of randomly oriented Halobacterium halobium purple membranes have raised new questions about the precise criteria which determine prohibition of the second harmonic. To address the problem a theoretical framework for SHG is developed that specifically deals with molecular systems, and is therefore cast in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…The paradox was resolved when it was shown that the unusually strong signal detected from isotropic suspensions, notably of purple membrane material, is attributable to optical coherence within the separate particles of the suspension [14]. As such, the harmonic emission displays an amalgam of the characteristics associated with full coherence (second harmonic generation) and incoherence (hyper-Rayleigh scattering).…”
Section: The Emergence Of Second Harmonic Signals From Randomly Orienmentioning
confidence: 99%
See 1 more Smart Citation
“…The paradox was resolved when it was shown that the unusually strong signal detected from isotropic suspensions, notably of purple membrane material, is attributable to optical coherence within the separate particles of the suspension [14]. As such, the harmonic emission displays an amalgam of the characteristics associated with full coherence (second harmonic generation) and incoherence (hyper-Rayleigh scattering).…”
Section: The Emergence Of Second Harmonic Signals From Randomly Orienmentioning
confidence: 99%
“…a significant intrinsic rigidity. Following the work of Andrews et al [14,15] the intensity of harmonic generation in the absence of prior optical excitation is given by the following expression:…”
Section: Harmonic Emission From Particles In Suspensionmentioning
confidence: 99%
“…In situations where such isotropy can be removed or is naturally lacking, SHG is allowed and can hence provide a very sensitive tool for detecting preferential molecular orientation. For example SHG has been used to gauge molecular orientation: at fluid interfaces [2,3]; within cell membranes [4,5]; of dipolar chromophores in poled polymers [6,7] and of molecules within molecular sieves [8]. In circumstances where preferential orientation arises, theory requires the application of suitably weighted three-dimensional rotational ensemble averages in order to arrive at the nett media response.…”
Section: Introductionmentioning
confidence: 99%
“…shows that the excited-state contribution bd (2) does not contain a vibrational resonance. This implies that as the visible pulse frequency ω 1 -ω eg is detuned away from the electronic resonance the signal must vanish along ω 1 -ω 2 )1070 cm -1 (Figure 3, parts A and C).The ground-state resonances do not show this cancellation (Figure 3, parts A and B).…”
Section: Frequency-domain (Cw) Signalsmentioning
confidence: 91%